A Focus on Macitentan in the Treatment of Pulmonary Arterial Hypertension. Issue 3 (5th June 2018) - Bedan, Martin; Grimm, Daniela; Wehland, Markus; Simonsen, Ulf; Infanger, Manfred; Krüger, Marcus
Abstract: The approval of macitentan has increased the number of pharmacological treatments of pulmonary arterial hypertension (PAH). Here, we review the effect on PAH of macitentan compared to other endothelin receptor antagonists. Drugs targeting the endothelin (ET) pathway include the selective ETA receptor antagonist ambrisentan, the ETA /ETB receptor antagonists, bosentan and macitentan, which were recently approved for PAH treatment. Macitentan exhibits higher antagonistic potency than bosentan and ambrisentan in pulmonary smooth muscle cells. Compared to ambrisentan and bosentan, macitentan has a longer duration of action, reflected by the longer half‐life, as well as pharmacodynamics attributed to its active metabolite, ACT‐132577. The efficacy of macitentan on PAH was investigated in the phase III SERAPHIN trial (NCT00660179). Macitentan significantly reduced morbidity and mortality. It improved the 6‐min. walk distance (6MWD) among PAH patients. In the AMB‐320/321‐E (NCT00578786) study, ambrisentan improved exercise capacity. In the EARLY study (NCT00091715), bosentan showed improvements in 6MWD which were not statistically significant. Bosentan had an effect on PAH in patients with Eisenmenger syndrome (ES) in the BREATHE‐5 study (NCT00367770), while macitentan did not improve 6MWD in these patients, but there are differences regarding study size and functional class, and that 30% of the patients treated with macitentan were already in treatment with a phosphodiesterase type 5 inhibitor. Macitentan revealed a lower risk of developing peripheral oedema and hepatotoxicity in the SERAPHIN study. In summary, macitentan has an efficiency comparable to bosentan and ambrisentan in the treatment of PAH. Patients treated with macitentan exhibited less adverse effects compared to bosentan and ambrisentan. In patients with PAH associated with ES, the trials with bosentan and macitentan do not seem comparable, and it needs to be clarified whether these drugs are effective when administered as part of a combination treatment in this condition.